EVALUASI TARIF ANGKUTAN UMUM PEDESAAN PADA TRAYEK TERMINAL LOKARIA – KECAMATAN TALIBURA - Fernando Nando; Alfrendo Satriawan Kabupung; Anastasia M. Noralita Soludale (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2021)
Public transportation which plays an important role in supporting the mobility of rural residents is rural public transportation. The function of rural public transportation is to serve rural communities in the fields of education, economy, and trade. Demand for transportation (rural transportation) will increase along with the increase in population and increased activity of people using transportation. Rural transportation income depends on the applicable fares and the number of passengers carried. Transport companies often experience losses due to very low tariffs. Thus, it is necessary to know the amount of the company's income according to the applicable rates per unit, per day, per month, and per year according to vehicle operational costs. The tariff amount is according to Sikka Regent's Decree Number 1 of 2022 concerning temporary tariffs for public passenger transportation within the Sikka Regency area. For the Lokaria Terminal route, Talibura sub-district, it is set at IDR 25,000/passenger/day and the fare on the ground is IDR 25,000/passenger/day, and for students IDR 15,000/passenger/day, and according to calculations based on Vehicle Operating Costs (BOK ) amounting to IDR 22,000/passenger/day while student passengers IDR 14,000/passenger/day.